The underexplored role of diverse stress factors in microbial biopolymer synthesis - Obruca, Stanislav; Sedlacek, Petr; Koller, Martin (Bioresource technology, 2021)
Polyhydroxyalkanoates (PHA) are microbial polyesters which, apart from their primary storage role, enhance the stress robustness of PHA accumulating cells against various stressors. PHA also represent interesting alternatives to petrochemical polymers, which can be produced from renewable resources employing approaches of microbial biotechnology. During biotechnological processes, bacterial cells are exposed to various stressor factors such as fluctuations in temperature, osmolarity, pH-value, elevated pressure or the presence of microbial inhibitors. This review summarizes how PHA helps microbial cells to cope with biotechnological process-relevant stressors and, vice versa, how various stress conditions can affect PHA production processes. The review suggests a fundamentally new strategy for PHA production: the fine-tuned exposure to selected stressors, which might be used to boost PHA production and even to tailor their structure.
Keywords: Polyesters; biotechnologie; polyhydroxyalkanoáty; Stress conditions; Biotechnological process; bioreaktory; polyestery; Waste substrates; Bioreactors; Temperature; Hormesis; Polyhydroxyalkanoates; Bacteria; teplota; Biotechnology